Um estudo sobre o consumo in-purchase em games mobile freemium no Brasil - Guerreiro, Robson Coelho (2024)
The objective of this study is to identify what leads consumers of freemium mobile games to make purchases within the game, thus, within the consumer's characteristics, verifying the variables that can influence purchase intention. The first part of the study carried out an RSL to find possible characteristics of mobile game players, in the second part of the study online data collection was carried out with 304 mobile game players. The data was used to verify the proposed hypotheses using the combination of partial least squares structural equation modeling (PLS-SEM), Sobel test, and necessary conditions analysis (NCA). The results confirm that all constructs, such as Socialization Affordances, Entertainment, Purchase Intention, Narcissism, Achievement and Game Addiction, presented loading values above 0.5, indicating good validity and reliability. The post-Bootstrapping results indicated significant relationships between the variables, with emphasis on the direct and indirect effects of Socialization Affordances, Entertainment, Achievement and Game Addiction on Purchase Intention. The necessary conditions analysis (NCA) revealed that, while some factors are crucial for Purchase Intention, with emphasis on Affordances and Gaming Addiction. Entertainment, socialization, narcissism and addiction have been found to be crucial to purchase intention. However, addiction, although profitable for companies, raises ethical questions due to the possible negative impacts on players' mental and financial health. The study highlights the need to balance the economic interest of developers with the well-being of users. These are important considerations for those intending to engage with consumption on technological platforms such as mobile games.